Epidemiology, Biodiversity, and Technological Trajectories in the Brazilian Amazon: From Malaria to COVID-19 - Codeço, Claudia T.; Dal'Asta, Ana P.; Rorato, Ana C.; Lana, Raquel M.; Neves, Tatiana C.; Andreazzi, Cecilia S.; Barbosa, Milton; Escada, Maria I. S.; Fernandes, Danilo A.; Rodrigues, Danuzia L.; Reis, Izabel C.; Silva-Nunes, Monica; et al. (Frontiers in Public Health, 2021)
The Amazon biome is under threat, with increasing rates of deforestation, loss of biodiversity and ecosystem services, high disease burden and social vulnerability. To counteract this process, we need to move beyond disciplines and create bridges between the ecological, economic and epidemiological dimensions of life. To contribute to this integrated perspective, we propose a systemic approach where epidemiological, economic and environmental trajectories are considered together. The municipalities of the Brazilian Amazon are classified in terms of their dominant technological trajectories, from peasant-based agriculture to large grain plantations. Different rates of forest conversion are found among trajectories. Incidence of vector-borne and environmental sensitive diseases vary along these trajectories as well. Malaria and dengue showed less ecological plasticity, with strong association with specific, although opposite, technological trajectories. Leishmaniasis, on the other hand, shows high ecological plasticity, being adapted to sylvatic, rural and urban environments. In 2020, the Covid19 epidemic struck the Amazon region very intensely, with fast dissemination to municipalities with monoculture and agroforest based economies. These patterns suggest distinct pathogenic complexes and public health challenges. By trekking changes in these three trajectories, one can monitor the ecosystem-human health in the different economic and social contexts of the Amazon.